The New Man Sport and corporatism between fascism and Italian Catholicism in the Portuguese Novo State between the two wars - Serapiglia, Daniele (Hispania Nova, 2019)
Between the two wars, Mihail Manoilsecu defined the 20th century as "the century of corporatism". In recent years, scholars have been focusing on the transnational dimension of corporatism, studying its doctrine and its effects on the social policies of different authoritarian regimes. So far, the most studied countries have been Italy and Portugal, the countries where the attempt to apply corporatist policies was most long-lasting. The interpreter of this corporatist society had to be the “new man”: sport was essential for his spiritual training. This article is based on sport education and it aims to demonstrate how sport was framed within the rhetoric of corporatism between the two wars.